Seed-Specific Expression of AtLEC1 Increased Oil Content and Altered Fatty Acid Composition in Seeds of Peanut (Arachis hypogaea L.) - Tang, Guiying; Xu, Pingli; Ma, Wenhua; Wang, Fang; Liu, Zhanji; Wan, Shubo; Shan, Lei (Frontiers in Plant Science, 2018)
Abstract: Peanut (Arachis hypogaea L.) is one of the major oil crops and is the fifth largest source of plant oils in the world. Numerous genes participate in regulating the biosynthesis and accumulation of the storage lipids in seeds or other reservoir organs, among which several transcription factors, such as LEAFY COTYLEDON1 (AtLEC1), LEC2, and WRINKLED1 (WRI1), involved in embryo development also control the lipid reservoir in seeds. In this study, the AtLEC1 gene was transferred into the peanut genome and expressed in a seed-specific manner driven by the NapinA full-length promoter or its truncated 230-bp promoter. Four homozygous transgenic lines, two lines with the longer promoter and the other two with the truncated one, were selected for further analysis. The AtLEC1 mRNA level and the corresponding protein accumulation in different transgenic overexpression lines were altered, and the transgenic plants grew and developed normally without any detrimental effects on major agronomic traits. In the developing seeds of transgenic peanuts, the mRNA levels of a series of genes were upregulated. These genes are associated with fatty acid biosynthesis and lipid accumulation. The former set of genes included the homomeric ACCase A (AhACC II), the BC subunit of heteromeric ACCase (AhBC4), ketoacyl-ACP synthetase (AhKAS II), and stearoyl-ACP desaturase (AhSAD), while the latter ones were the diacylglycerol acyltransferases and oleosins (AhDGAT1, AhDGAT2, AhOle1, AhOle2, and AhOle3). The oil content and seed weight increased by 4.42%–15.89% and 11.1%–22.2%, respectively, and the levels of major fatty acid (FA) components including stearic acid, oleic acid, and linoleic acid changed significantly in all different lines.